Evaluation of Awareness about Hematuria among Non-Urologist Doctors - Hira Bumbia, Atif Javaid, Quratulain Badar, Niaz Soomro, Abdul Rehman, Sajan Khan (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: To evaluate the attitude, general level of knowledge and practices regarding the common urological problems in non urological doctors Methodology: A cross-sectional study was carried out in multiple tertiary care hospitals and private clinics between August 2018 to December 2019. All the general physicians having their private practice or those working in Agha Khan University Hospital, Civil Hospital Karachi, Liaquat National Hospital, Jinnah postgraduate hospital, and Ziauddin Hospital were included in the study. General physicians belonging to the urology department were excluded from the study. Results: Most of the doctors could easily diagnose gross hematuria (55.17%) but microscopic hematuria was missed by many(34.96%). Risk assessment of bladder carcinoma like smoking , any chemical exposure , previous history of hematuria etc was not addressed by the majority of gynecologists (69.03%), physicians(52.54%) as well as internists (32.72%). While most physicians assess gross hematuria by ultrasound, microscopic hematuria is not further investigated by a significant percentage of physicians. During survey it was revealed that most of the physicians use antibiotics as the the mainstay of treatment for hematuria without considering the urine c/s and cytology. Conclusion: A trend of overuse of antibiotics and reluctance of primary care doctors in referring the patient to the specified doctor was seen. It was noted that there is a lack of understanding and knowledge among non urological doctors regarding a common sign.